Smart Medical Monitoring System Based on Arduino and Medical Sensors - Mohamed, Karrar Humam Makki; Hasson, Shahad Hyder Mohammed; Hassan, Muqtada Ali Hussein (American Journal of Botany and Bioengineering, 2025)
With the advent of the communications and information revolution, the integration of the Internet of Things (IoT) and Artificial Intelligence (AI) has become crucial across various aspects of life. The adoption of these technologies is now a vital requirement to keep pace with the significant advancements in communication, thereby enhancing modern human existence. IoT represents a rapidly evolving technology that finds applications in numerous fields, including agriculture, industry, and healthcare. Medical facilities can leverage this technology to monitor and analyze the activities of individuals and patients via mobile devices such as smartphones and wearable wireless technologies connected to the Internet, thereby facilitating the development of intelligent systems that offer a more precise understanding of human activity throughout the day. In the current study, a Smart Monitoring Health (SMH) system was designed and built based on IoT using ESP8266 for wireless communication, which can measure the patient’s heart rate/pulse (BPM) and blood oxygen level (SpO2) using the MAX30100 pulse oximeter sensor, as well as measure body temperature using the MLX90614 temperature sensor. The system is controlled through Arduino.